2007
DOI: 10.1080/09537100600944277
|View full text |Cite
|
Sign up to set email alerts
|

Variables influencing Multiplate™ whole blood impedance platelet aggregometry and turbidimetric platelet aggregation in healthy individuals

Abstract: We investigated the relationship between impedance platelet aggregometry (IPA) as measured by the Multiplate system and turbidimetric platelet aggregation (TPA) induced by ADP, arachidonic acid (AA), and collagen; blood cell counts; platelet function analyzer (PFA-100) closure times (CT), and von Willebrand factor (VWF) in 120 well-characterized healthy individuals. Pre-analytical and analytical conditions were standardized comprehensively. Analytical reliability of IPA and TPA and the influence of pre-analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
103
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 18 publications
15
103
4
Order By: Relevance
“…Previous studies of healthy volunteers and patients with stable CAD have found that TPC affects Multiplate results, especially when platelet counts are low, but no studies have been identified that tested the blood of patients with actual thrombocytopenia [1][2][3][4][15][16][17]. We found a significant association between TPC and AUC for all four agonists in patients with severe thrombocytopenia, which is in concordance with previous studies in healthy volunteers and CAD patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies of healthy volunteers and patients with stable CAD have found that TPC affects Multiplate results, especially when platelet counts are low, but no studies have been identified that tested the blood of patients with actual thrombocytopenia [1][2][3][4][15][16][17]. We found a significant association between TPC and AUC for all four agonists in patients with severe thrombocytopenia, which is in concordance with previous studies in healthy volunteers and CAD patients.…”
Section: Discussionsupporting
confidence: 82%
“…Würtz, et al [2] and Rubak, et al [4] also found a significant effect of WBC on AUC. Seyfert, et al [15] did not find a significant effect of WBC on AUC in a study on healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The fluids were mixed in a measuring cuvette for 3 min at a constant temperature of 37°C (Mueller et al, 2007;Seyfert et al, 2007). To determine aspirin resistance, arachidonic acid as an inducer was added at a final concentration of 15 mM.…”
Section: Multiple Electrode Aggregometrymentioning
confidence: 99%
“…Nowadays, the so-called golden standard is platelet aggregation testing in platelet-rich plasma (PRP) using light transmission aggregometry (Cattaneo, 2007;Cattaneo et al, 2007). A novel option for determining residual platelet aggregation is the use of multiple electrode aggregometry (MEA) in whole blood (Mueller et al, 2007;Seyfert et al, 2007). It measures electrical impedance between two electrodes in hirudin-treated whole blood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lack of standardised cut-offs makes interpretation of different studies difficult, although a good correlation between several methods and the LTA was shown (60,67). Two potential candidates to fulfil clinical needs are the Accumetrics VerifyNow Clopidogrel (P2Y 12 ) assay (68) and the multiple electrode platelet aggregometry (MEA) (69) , which are easy to use and rapid tests appropriate for the acute setting. The MEA implements the principle of impedance aggregometry with no need for blood centrifugation and the ability to assess platelet function in ~ 10 minutes (64).…”
Section: Clinical Focusmentioning
confidence: 99%